Biophilic and Bioclimatic Architecture Analytical Therapy for the Next Generation of Passive Sustainable Architecture - Almusaed, Amjad; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2011)
The concept of biophilic and bioclimatic architecture represents one of the most promising ideas in sustainable building. Together with its consideration of ecologically harmless materials and use of renewable energy sources, it brings an enormous quality increase in planning and workmanship, as well as an improvement in inhabitants$1 (Bcomfort. This valuable concept merits a dedicated discussion. Biophilic and Bioclimatic Architecture outlines a new movement that aims to create environmentally-friendly, energy-efficient buildings and developments by effectively managing natural resources. The book has three parts: Part I focuses on the impact of human needs on the creation process and assesses the concept of value in architectural hypotheses. Part II opens the way to a new understanding of biophilic architecture as a response to destructive human activities and also considers the side effects of using natural resources. Part III shows the significant benefits of making the connection between climate and comfort that can be achieved through bioclimatic architecture. Biophilic and Bioclimatic Architecture will enable architects, engineers and other specialists to develop innovative, sustainable architectural designs.s
1. Overview -- 2. Architectural Hypothesis -- 3. Architectural Theory -- 4. Biophilic Architecture Hypothesis -- 5. Introduction on Plants and Vegetations -- 6. Introduction on Growing Media (Soil) -- 7. Introduction on Irrigation Systems -- 8. Green Areas in Biophilic Architecture -- 9. Climate Change and Human Health (The Challenges and Remediation Act) -- 10. The Urban Heat Island Phenomenon Effects Upon Urban Components -- 11. The Green Areas Benefits Upon Urban Sustainability Role -- 12. Plants, Oxygen and Human Life Benefits -- 13. Evapo-Transpiration and Environmental Ameliorate Benefits -- 14. Socio and Healthy Human Psychology Upon Biophilic Architecture -- 15. Green Roofs -- 16. Green Walls -- 17. Interaction Between Architectural Creation and Environmental Impact -- 18. Vernacular Architecture and Human Experiences -- 19. Vernacular Architecture from Hot Regions (Basrah - Iraq) -- 20. Vernacular Architecture from Cold and Temperate Regions (Aarhus - Denmark) -- 21. Improvement of Exterior and Interior Energy Allocate -- 22. Improvement of Thermal Insulation (Passive Buildings) -- 23. Improvement of Energy Saving Concept -- 24. Windows Between Optical and the Thermal Roles -- 25. Illuminations by Sun-Skylight- Tubes -- 26. Illumination by Optical Arteries -- 27. Illuminate by Light Shelves -- 28. Cooling by Effective Shading -- 29. Cooling by Comfort Ventilation -- 30. Cooling by Direct Evaporative Systems -- 31. Cooling by Indirect Evaporative Systems -- 32. Cooling by Thermal Earth Inertia -- 33. Passive Heating Concept -- 34. Solar Passive Heating Components -- 35. Passive Heating Systems -- 36. Remembering Conclusion.
Keywords: Architecture; Regional planning; Urban planning; Civil engineering; Sustainable development; Architecture / Design; Architectural History and Theory; Sustainable Development; Civil Engineering; Landscape/Regional and Urban Planning; Electronic books